Necesidad de reformar el artículo 153 del Código De Trabajo con la finalidad de que exista estabilidad laboral de la mujer que se encuentra en periodo de lactancia - Díaz Tandazo, Yadira Mercedes (2015)
The woman today has accomplished many achievements regarding gender discrimination that exists in society at large, this also happens in the workplace, where it is true it has protected the pregnant woman not to the woman is breastfeeding, which is separate from their work without any consideration. There is corresponding to the woman who is breastfeeding to use two hours of work and can feed your baby leave, but it there is no guarantee for stability, since this permission is a negative circumstance for companies reason which opt for replacement. Art. 153 of the Labour Code states regarding the protection of pregnant women, but does not refer to the woman who is in a state of infancy, which means a lack of protection for this sector of women who are attending their children in their first months of life, protection is vital for breeding, as well that I did not do it and not being able to prevent this situation Ecuadorian women to be separated from unfair way of their work is a legal situation that should change in the Labor Code. The whole family is protected in their rights from the Constitution of the Republic of Ecuador, as well as existing international treaties, but there is nothing about this in the Labour Code, so I think that this should change radically